Conservation for the Anthropocene ocean : interdisciplinary science in support of nature and people - Levin, Phillip S.; Poe, Melissa R.; ScienceDirect eBooks (London, United Kingdom : Academic Press, an imprint of Elsevier, 2017)
Conservation for the Anthropocene Ocean: Interdisciplinary Science in Support of Nature and People emphasizes strategies to better connect the practice of marine conservation with the needs and priorities of a growing global human population. It conceptualizes nature and people as part of shared ecosystems, with interdisciplinary methodologies and science-based applications for coupled sustainability. A central challenge facing conservation is the development of practical means for addressing the interconnectedness of ecosystem health and human well-being, advancing the fundamental interdisciplinary science that underlies conservation practice, and implementing this science in decisions to manage, preserve, and restore ocean ecosystems. Though humans have intentionally and unintentionally reshaped their environments for thousands of years, the scale and scope of human influence upon the oceans in the Anthropocene is unprecedented. Ocean science has increased our knowledge of the threats and impacts to ecological integrity, yet the unique scale and scope of changes increases uncertainty about responses of dynamic socio-ecological systems. Thus, to understand and protect the biodiversity of the ocean and ameliorate the negative impacts of ocean change on people, it is critical to understand human beliefs, values, behaviors, and impacts. Conversely, on a human-dominated planet, it is impossible to understand and address human well-being and chart a course for sustainable use of the oceans without understanding the implications of environmental change for human societies that depend on marine ecosystems and resources. This work therefore presents a timely, needed, and interdisciplinary approach to the conservation of our oceans.
1. Bridging the science-policy interface: adaptive solutions in the Anthropocene / J.M. Sullivan, E.B. Cerny-Chipman, A.A. Rosenberg, J. Lubchenco -- 2. Climate variability, climate change, and conservation in a dynamic ocean / M.L. Pinsky, R.L. Selden -- 3. The future species of Anthropocene seas / N.K. Dulvy, H.K. Kindsvater -- 4. How can the oceans help feed 9 billion people? / J.Z. Koehn, E.H. Allison, N. Franz, E.S. Wiegers -- 5. Social resilience in the Anthropocene ocean / E.M. Finkbeiner, K.L.L. Oleson, J.N. Kittinger -- 6. Principles for interdisciplinary conservation / H.M. Leslie -- 7. Creating space for community in marine conservation and management: mapping "communities-at-sea" / K. St. Martin, J. Olson -- 8. Conservation actions at global and local scales in marine social-ecological systems: status, gaps, and ways forward / N.C. Ban, C. Whitney, T.E. Davies, E. Buscher, D. Lancaster, L. Eckert, C. Rhodes, A.L. Jacob -- 9. Ocean cultures: Northwest coast ecosystems and indigenous management systems / D.L. Mathews, N.J. Turner -- 10. Blurred lines: what's a non-native species in the Anthropocene ocean? / I.M. Cote -- 11. Can ecosystem services make conservation normal and commonplace? / K.M.A. Chan, P. Olmsted, N. Bennett, S.C. Klain, E.A. Williams -- 12. Beyond privatization: rethinking fisheries stewardship and conservation in the North Pacific / R. Donkersloot, C. Carothers -- 13. Addressing socioecological tipping points and safe operating spaces in the Anthropocene / B.S. Halpern -- 14. Stakeholder participation in marine management: the importance of transparency and rules for participation / C. Rockmann, M. Kraan, D. Goldsborough, L. van Hoof -- 15. Marine conservation as complex cooperative and competitive human interactions / S. Basurto, E. Blanco, M. Nenadovic, B. Vollan -- 16. Transdisciplinary research for conservation and sustainable development planning in the Caribbean / K.K. Arkema, M. Ruckelshaus -- 17. Social-ecological trade-offs in Baltic Sea fisheries management / R. Voss, M.F. Quaas, J. Hoffmann, J.O. Schmidt -- 18. Human rights and the sustainability of fisheries / S.G. Lewis, A. Alifano, M. Boyle, M. Mangel -- 19. Implications of a changing climate for food sovereignty in coastal British Columbia / T. Satterfield, L. Robertson, N. Vadeboncoeur, A. Pitts -- 20. The future of modelling to support conservation decisions in the Anthropocene ocean / E.E. Plaganyi, E.A. Fulton -- 21. The big role of coastal communities and small-scale fishers in ocean conservation / A. Charles -- 22. Innovations in collaborative science: advancing citizen science, crowdsourcing and participatory modeling to understand and manage marine social-ecological systems / S. Gray, S. Scyphers -- 23. Looking forward: interconnectedness in the Anthropocene ocean / M.R. Poe, P. Levin.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 17, 2018).
Elsevier
Keywords: Marine resources conservation; Ocean and civilization; SCIENCE / Earth Sciences / Geography; SCIENCE / Earth Sciences / Geology; Marine resources conservation; Ocean and civilization; Electronic books